السؤال
الحل
y + 2 2 y − 4 ÷ y 3 + 8 y − 2
y + 2 2 y − 4 ÷ y 3 + 8 y − 2 = ( y + 2 ) 2 ( y − 2 ) × y − 2 ( y + 2 ) ( y 2 − 2 y + 4 ) = 1 2 ( y 2 − 2 y + 4 )
x+512x×6x−30x2−25=x+512x×6(x−5)(x−5)(x+5)=12x
3−x4−2x×x2+x−69−x2=3−x−2(x−2)×(x+3)(x−2)(3−x)(3+x)=−12
y2−7yy3−27÷y2−49y2+3y+9=y(y−7)(y−3)(y2+3y+9)×y2+3y+9(y−7)(y+7)=y(y−3)(y+7)
5x2−36−2x2−12x+36=5(x−6)(x+6)−2(x−6)2=5(x−6)−2(x+6)(x−6)2(x+6)=5x−30−2x−12(x−6)2(x+6)=3x−42(x−6)2(x+6)
3x−2−2x−2+4+2x+x2x3−8=1x−2+4+2x+x2(x−2)(x2+2x+4)=1+1x−2=2x−2
تم حفظ السؤال في محفظة الأسئلة
لايمكن حفظ السؤال لانه خارج الصف المحدد من قبلكم